A Systematic Framework for Designing Persuasive Mobile Health Applications Using Behavior Change Wheel - Sari H.; Othman M.; Sulaiman H. (Springer, 2023)
Mobile technology holds great potential for designing effective health behavior interventions. Changing individuals behavior and attitude is a growing research topic in the fields of behavioral science and information technology. Persuasive technology (PT), which defined as the technology intended to alter individuals attitude or behavior, has a beneficial influence on changing users behavior and can lead to a better outcome. Persuasive techniques and models have been utilized to design behavioral change interventions in several contexts, including health care. Among them, the persuasive system model (PSD model) has been widely used in developing persuasive applications. Despite the potential, the PSD model has been criticized for lack of theoretical and evidence basis, which limit its capability in designing effective persuasive applications. Behavior change wheel (BCW) considered a comprehensive systematic framework used behavior techniques to develop behavior change interventions. This study aims to propose an integrated conceptual framework combining PSD and BCW, which could be used to implement successful persuasive mobile health applications. Springer Nature Singapore Pte Ltd. 2020.